Bagaimana Strategi Pemasaran Rumah Sakit di Indonesia Agar Bisa Diakui di Dunia Internasional? - Komariah Hildayanti, Siti; Mufid, Faris Anas; Sari, Ega Widiya (Widya Manajemen, 2025)
This study aims to analyze and formulate effective marketing strategies for hospitals in Indonesia to be recognized internationally. In facing global competition, Indonesian hospitals need to improve service quality and develop marketing strategies based on digital technology to reach international patients. Digital marketing through social media and websites plays a crucial role in expanding the hospital's reach in the global market. Furthermore, strong branding and leveraging international accreditations, such as Joint Commission International (JCI), are essential for enhancing the hospital's image internationally. This research identifies challenges faced by Indonesian hospitals, such as limited digital infrastructure and human resource skills in international marketing. The research method used is a literature review, analyzing various sources from journals, articles, and reports related to hospital marketing, digital marketing, branding, and international accreditation. The results show that Indonesian hospitals need to adopt stronger digital marketing strategies to compete in the international market. Digital marketing and social media are effective tools for reaching international patients, while branding that emphasizes service quality and local culture is also key. However, challenges related to infrastructure and marketing skills need to be addressed to optimize the global market potential.